2012
DOI: 10.5489/cuaj.19
|View full text |Cite
|
Sign up to set email alerts
|

Evolving therapeutic strategies for premature ejaculation: The search for on-demand treatment – topical versus systemic

Abstract: Premature ejaculation (PE) is a common sexual dysfunction affecting 20% to 30% of men worldwide. Definitions of PE vary, but it is typically characterized by short intravaginal ejaculatory latency time (IELT) with concomitant sexual dissatisfaction and distress. PE may be lifelong or acquired, but its etiology remains unclear. Treatment of PE typically involves pharmacotherapy, particularly when lifelong. Although there are numerous reports on the offlabel use of selective serotonin reuptake inhibitors (SSRIs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…3,4 Prolongation of intravaginal ejaculation latency time by SSRI has been reported by many previous studies. 2,5 According to results of present study, the authors concluded that an elevated serum melatonin level might be the reason for improvement of PE.…”
Section: Editorial Comment Editorial Comment From Dr Sato To Relationmentioning
confidence: 95%
See 1 more Smart Citation
“…3,4 Prolongation of intravaginal ejaculation latency time by SSRI has been reported by many previous studies. 2,5 According to results of present study, the authors concluded that an elevated serum melatonin level might be the reason for improvement of PE.…”
Section: Editorial Comment Editorial Comment From Dr Sato To Relationmentioning
confidence: 95%
“…2,5 According to results of present study, the authors concluded that an elevated serum melatonin level might be the reason for improvement of PE.…”
mentioning
confidence: 95%